HEAT STABILITY OF DIFFERENT PIG BREEDS - Usachova, V. Ye.; Gyria, V. M.; Rak, T. M.; Siabro, A. S.; Pavlova, I. V. (Scientific Progress & Innovations, 2020)
Heat stress limits animal productivity, negatively affects their well-being, influences production, and causes considerable losses. The aim of the studies was to conduct index evaluation of heat stability and thermal stress sensitivity of various pig genotypes, which to some extent disclose their adaptive ability at using different methodical approaches. It has been established that according to the index of adaptive ability (Іa), fattening young animals of Red White-Belted (RWB) breed have higher index in comparison with Land-race pig breed by 29.5% and Pietrain – by 53.3 %. According to heat sensitivity index (HSI), it has been found that the given genotype was the least affected by heat action, which exceeded reliably (Р≤0.1) the ana-logs of Pietrain and Landrace breeds by 12.4 and 15.3 %, respectively. The animals of this breed also had higher fattening indicators among all experimental groups. As to the age of reaching 100 kg of live weight they exceeded Pietrain and Landrace breeds by 11 (5.7 %, Р≤0.05) and 4 days (2.7 %), respectively; accord-ing to the average daily weight gain – by 73.7 g (9.9 %, Р≤0.01) and 12 g (1.5 %); as to feed consumption per 1 kg of gain - by 0.22 feed units (5.8 %, Р≤0.01) and 0.08 feed units. Animals’ estimation using the index of thermal stress tolerance (ITST), developed by us, has shown that the majority of RWB breed gilts (71.1 %) had the status of thermal stress neutral (ITST=4.3) in correlation of 2.5:1 to thermal stress tolerant animals (ITST=15.94) and complete absence of heat stress sensitive gilts. In the experimental group of Pietrain pig breed the level of thermal stress neutral animals (ITST=3.95) made 57.1% and was by 14.2% less than of thermal stress sensitive animals (ITST=1.73), and thermal stress tolerant animals were absent. Among fatten-ing gilts of Landrace breed, the same level (42.9 %) of thermal stress neutral (ITST=2.31) and thermal stress sensitive animals (ITST=1.63) was registered; as to the index of thermal stress tolerance, (ITST=17.42) they somewhat differed from RWB breed. On the average, depending on genotypes, thermal stress sensitive young animals had reliably (Р≤0.01) higher body temperature and heart rate. It has been revealed that all thermal stress sensitive pig genotypes are characterized by high heart contraction rate during fixation – 214.8–220.2 heart beats/ min, which was 79.9 – 82.0 heart beats /min more than heart rate of thermal stress tolerant gilts of the same age (Р≤0.001). At the same time, thermal stress neutral animals had by 27.1% reliably lower indices of heat beat in comparison with thermal stress sensitive animals. In our research no correlation be-tween the index of thermal stress sensitivity (ITST) of animals and their fattening qualities was revealed.